(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to know the level of a sense of loneliness among the elderly residents in social care homes, and to know the differences in the degree of loneliness between males and females, as it aimed to detect the differences in the sense of loneliness depending on the variables; of social situation, and age. In This research it is used Loneliness scale of preparation by the researcher. The researcher extracted the validity and reliability for the scale of Loneliness. The scale is applied in social care homes in the cities of Latakia and Tartous. The sample consisted of (32) elderly 12 males and 20 female. The research is found the following results: The level of a sense of loneliness is average, and there is no statistically significant differences in the sense of loneliness between males and females, as too there are no statistically significant differences in the sense of loneliness depending on the variables of the age for the research sample, and there are statistically significant differences in the sense of loneliness depending on the variables of the social situation.